2014
DOI: 10.3390/ma7021201
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric Sugar Sensing Using Boronic Acid-Substituted Azobenzenes

Abstract: In association with increasing diabetes prevalence, it is desirable to develop new glucose sensing systems with low cost, ease of use, high stability and good portability. Boronic acid is one of the potential candidates for a future alternative to enzyme-based glucose sensors. Boronic acid derivatives have been widely used for the sugar recognition motif, because boronic acids bind adjacent diols to form cyclic boronate esters. In order to develop colorimetric sugar sensors, boronic acid-conjugated azobenzenes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 105 publications
(87 reference statements)
1
47
0
Order By: Relevance
“…Successful boronic acid sugar receptors used in direct sensing are often multivalent in order to overcome the high solvation enthalpies of sugars in water. [14][15][16] To increase the solubility of such receptors in water, the boronic acids have been covalently linked to water-soluble polymers, 17 or bound to a charged moiety. 18 Selectivity has been typically difficult to achieve.…”
Section: Introductionmentioning
confidence: 99%
“…Successful boronic acid sugar receptors used in direct sensing are often multivalent in order to overcome the high solvation enthalpies of sugars in water. [14][15][16] To increase the solubility of such receptors in water, the boronic acids have been covalently linked to water-soluble polymers, 17 or bound to a charged moiety. 18 Selectivity has been typically difficult to achieve.…”
Section: Introductionmentioning
confidence: 99%
“…PBA reacts with cis-diol functional groups of sugars to form a five-or six-membered ring via ester bonds. As a result, PBA derivatives have been widely investigated as sugar-recognition motifs in chemical probes for sugar analysis [27][28][29][30][31][32] and sugar-sensitive Ins release systems [33][34][35]. We recently synthesized PBA-modified CyDs (PBA-CyDs) and found that they form supramolecular structures [36].…”
Section: Introductionmentioning
confidence: 99%
“…The boronate form can interact with the diol moiety of a polyol to form a cyclic ester; the reaction is rapid and reversible, and a state of equilibrium can therefore be achieved depending on the concentration of the polyol [14]. Utilizing this rapid and reversible reaction of PBA, analytical chemists have attempted to create chemical sensors to monitor blood D-glucose (Glc) levels [15][16][17][18]. Furthermore, some pharmaceutical scientists have attempted to incorporate PBA as a sugar recognition motif into insulin delivery systems in which the interaction between PBA and Glc is expected to function as a trigger for insulin release [19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%